Functional levels and MRI patterns of muscle involvement in upper limbs in Duchenne muscular dystrophy. - Claudia Brogna; Lara Cristiano; Tommaso Tartaglione; Tommaso Verdolotti; Lavinia Fanelli; Luana Ficociello; Giorgio Tasca; Roberta Battini; Giorgia Coratti; Nicola Forcina; Roberto De Santis; Giulia Norcia; et al. (PLoS ONE, 2018)
The aim of the study was to evaluate the spectrum of upper limb functional activities and imaging finding in a cohort of patients affected by Duchenne muscular dystrophy. Thirty-one patients of age between 5 and 29 years were included in the study (17 ambulant and 14 non-ambulant). They were all assessed using the Performance of Upper Limb (PUL) test and muscle MRI of shoulder, arm and forearm in order to establish if the functional scores obtained at shoulder, mid and distal level related to specific patterns of involvement in each upper limb segment on muscle MRI. At shoulder level, latissimus dorsi, serratus anterior, infraspinatus and subscapularis were always involved, even in patients with full functional scores at shoulder level. Diffuse and severe involvement of all muscles was found in the patients with a PUL shoulder functional score of ≤ 5. At arm level biceps brachii, brachialis and triceps were generally concordantly involved or spared. Some degree of involvement could already be detected in patients with reduced scores on the PUL mid domain. They were generally severely involved in patients with functional scores less than 6 at mid-level. At distal level supinator and pronator muscles were often involved, followed by brachioradialis and, less frequently, by the muscles of the flexor compartment. The extensor muscles were generally completely spared. A diffuse and severe involvement was found only in patients who had very low scores (8 or below) on the PUL distal domain. The integrated use of functional scales and imaging allowed to establish patterns of involvement at each level, and the functional scores that were more frequently associated with diffuse and severe involvement.